GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 1821 species occurrences available in GBIF matching the query: TaxonKey: Cornus florida L. BasisOfRecord: Specimen or Living Specimen. The dataset includes 1821 records from 79 constituent datasets: 1 records from The Vascular Plants Collection of the Regensburgische Botanische Gesellschaft. 75 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 8 records from Phanerogamic Botanical Collections (S). 3 records from IAC - Herbário do Instituto Agronômico de Campinas. 131 records from Naturalis Biodiversity Center (NL) - Botany. 2 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 2 records from SPF - Herbário da Universidade de São Paulo. 1 records from Herbario Universidad de Antioquia (HUA). 17 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 13 records from MBM - Herbário do Museu Botânico Municipal. 1 records from OHN. 16 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 3 records from Australia's Virtual Herbarium. 1 records from Natural History Museum Maastricht (NL) - Herbarium. 5 records from Consortium of California Herbaria. 133 records from CONN. 71 records from H.A. Stephens Herbarium. 2 records from University of Lethbridge Herbarium (LEA). 2 records from University of California Museum of Paleontology. 1 records from ALCB - Herbário Alexandre Leal Costa. 88 records from NMNH occurrence DwC-A. 1 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 21 records from OAC-BIO Herbarium. 1 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 3 records from Jardin botanique de Montréal (JBM). 9 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 1 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 301 records from Tropicos Specimen Data. 3 records from Natural History Museum (London) Collection Specimens. 2 records from Fundación Carl Faust: Herbario del Jardí Botànic Marimurtra: HMIM. 5 records from NatureServe Network Species Occurrence Data. 1 records from Plant Specimens of Oiso Municipal Museum. 2 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 2 records from Ibaraki Nature Museum, Vascular Plants collection. 2 records from Botanical Garden Collection. 1 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 26 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 5 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 1 records from Jardín Botánico de Córdoba: Herbarium COA. 1 records from Aranzadi Zientzi Elkartea. 3 records from Auckland Museum Botany Collection. 1 records from Botanic Garden of the Finnish Museum of Natural History. 5 records from herbario. 35 records from University of Copenhagen Arboretum. 1 records from DAV UC Davis Center for Plant Diversity. 45 records from Herbarium (UNA). 7 records from Herbarium Berolinense. 1 records from The Erysiphales Collection at the University Halle-Wittenberg. 19 records from Harvard University Herbaria. 1 records from EURISCO, The European Genetic Resources Search Catalogue. 7 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 6 records from Plant specimens depodited in Osaka Museum of Natural History, Japan.. 126 records from USF Herbarium. 1 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 28 records from Field Museum of Natural History (Botany) Seed Plant Collection. 2 records from UA Herbarium. 39 records from R. L. McGregor Herbarium Vascular Plants Collection. 1 records from Biological and palaeontological collection and observation data MNHNL. 34 records from Botany Division, Yale Peabody Museum. 5 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 2 records from UPCB - Herbário do Departamento de Botânica. 1 records from Royal Museum of Central Africa - Metafro-Infosys - Xylarium. 121 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 3 records from Bernice P. Bishop Museum. 1 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 2 records from Royal Botanic Garden Edinburgh Herbarium (E). 61 records from Michigan State University Herbarium Vascular Plants. 4 records from Botany (UPS). 9 records from University of British Columbia Botanical Garden Collections (UBCBG). 1 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 32 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 2 records from Wilson Botanical Garden - Las Cruces Biological Station. 77 records from Green Plant Herbarium (TRT). 63 records from SysTax - Botanical Gardens. 5 records from Vascular Plant Herbarium, Oslo (O). 3 records from E. C. Smith Herbarium (ACAD). 100 records from BUT Friesner Herbarium. 2 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 1 records from UESC - Herbário Universidade Estadual de Santa Cruz.
Keywords: GBIF; biodiversity; species occurrences